2021
DOI: 10.3390/jcs5070177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wood Fiber Surface Treatment on the Properties of Recycled HDPE/Maple Fiber Composites

Abstract: This work reports on the production and characterization of recycled high density polyethylene (R-HDPE) composites reinforced with maple fibers. The composites were produced by a simple dry-blending technique followed by compression molding. Furthermore, a fiber surface treatment was performed using a coupling agent (maleated polyethylene, MAPE) in solution. FTIR, TGA/DTG, and density analyses were performed to confirm any changes in the functional groups on the fiber surface, which was confirmed by SEM-EDS. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
2
10
1
Order By: Relevance
“…So MAPE helps to reduce the polarity/hydrophilicity difference between the matrix and natural fibers leading to improved phase compatibility (more similar polarity and chemical bonding between the active groups) [ 34 ]. Similar results have been reported for fiber/rubber dispersion, and filler/matrix adhesion (interactions) using MAPE as a compatibilizer in rHDPE/maple wood fibers [ 35 ] and maleated polyethylene/GTR/wood flour composites [ 36 ]. For the processing method effect, the tensile strength of injection molded R40F* (9.2 MPa) is 20% higher than that of the compression molded sample (7.4 MPa) with the same composition.…”
Section: Resultssupporting
confidence: 83%
“…So MAPE helps to reduce the polarity/hydrophilicity difference between the matrix and natural fibers leading to improved phase compatibility (more similar polarity and chemical bonding between the active groups) [ 34 ]. Similar results have been reported for fiber/rubber dispersion, and filler/matrix adhesion (interactions) using MAPE as a compatibilizer in rHDPE/maple wood fibers [ 35 ] and maleated polyethylene/GTR/wood flour composites [ 36 ]. For the processing method effect, the tensile strength of injection molded R40F* (9.2 MPa) is 20% higher than that of the compression molded sample (7.4 MPa) with the same composition.…”
Section: Resultssupporting
confidence: 83%
“…This effect essentially upcycles the material. Notably, the level of enhancement achieved in this study surpassed that reported in comparable works [ 39 , 55 , 56 , 57 ]. While the previous sections provided qualitative reasoning for the high reinforcing efficiency of PALF, we will now delve into a quantitative analysis using a micromechanical model and compare our findings with published data from similar systems.…”
Section: Discussion and Application Example Of Rhdpe Compositecontrasting
confidence: 78%
“…For composites, the fracture surface clearly shows the alignment of both NFM ( Figure 12 c,d) and PALF ( Figure 12 g,h) in the same direction as the machine direction (toward the observer). This alignment is an important criterion that improves the filler’s reinforcement efficiency significantly compared to other works [ 39 , 55 , 56 , 57 ]. The gap between the filler and the matrix and the filler pull-out, due to poor compatibility, can be seen in both composites.…”
Section: Resultsmentioning
confidence: 99%
“…Fletes and Rodrigue published a study on the synthesis and characterization of recycled high‐density polyethylene (R‐HDPE) composites reinforced with maple fibres. [ 136 ] They also looked at the effect of surface treatment on reinforced R‐HDPE composites and found that the tensile modulus, flexural modulus, tensile strength, flexural strength, and impact resistance all improved by 23%, 54%, 26%, 46%, and 87%, respectively. The University of Waterloo's Institute of Polymer Research investigated a sustainable method for fabricating thin‐layered wood‐based biocomposites with polylactic acid (PLA) binder using a solvent blending process at high wood fibre concentrations (50–80 wt.%).…”
Section: Bioproducts From Woodmentioning
confidence: 99%